Pengembangan Instrumen Penilaian Proses Menggunakan Model ADDIE - Handoko; Rohman, Fatkhur; Rahman, Sapta Isniar; Rahmawati, Dina; Sucitra, Diah Ayu (Arus Jurnal Pendidikan, 2025)
Field evidence shows that most lecturers do not yet have specific guidelines for assessing students' process skills, so that assessment remains subjective and oriented towards final results. In fact, the main objective of project-based learning is to develop critical thinking, collaboration, and creativity skills. This study aims to develop an objective, consistent, and transparent process assessment rubric using the ADDIE model. The research participants included 5 lecturers and 72 students from project-based classes. Data were collected through interviews, observations, and documentation, then validated by experts and tested for reliability. The results showed that the rubric instrument obtained an average validity of 97% (highly valid) and practicality and effectiveness of 90.25% (highly effective). This rubric contains 21st-century skill indicators and is equipped with an informative reporting system, enabling it to provide constructive feedback to students. Thus, the developed process assessment rubric not only improves the objectivity and consistency of evaluation but also supports the achievement of project-based learning objectives in higher education.